Dinâmica estrutural de uma savana amazônica sob diferentes regimes de queimada - Deus, Ygo Silvestre de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2011)
Savanna-forest dynamics have been studied in many tropical regions of world. Drought combined with anthropogenic effects may increase the coverage of Amazonian savannas under predicted global-warming scenarios. We used permanent plots in a vegetation mosaic in the Alter do Chão region, Pará State, Brazil, to investigate savanna-forest succession dynamics. We assessed the tree structural dynamics and species composition in periods with and without fires, to evaluate how establishment of forest and savanna trees. Fires maintain or reduce tree recruitment, and periods without fire are necessary to increase tree cover. However, forest species grow faster than savanna species during periods without fires, and this result in quick savanna encroachment. Species typical of the savanna-forest boundary provide conditions for establishment of long-live forest species by clump formation pathway. But species typical of Amazonian secondary forests participated little in the early successional stages.
Keywords: Dinâmica estrutural; Queimadas na Savana Amazônica; Espécies savânicas